The impact of job satisfaction on employees' performance in divisional secretariat of jaffna - Gnanabasharan, K.; Reginold, S.E. (University of Jaffna, 2016)
The success and survival of an organization depends on effective utilization of resources. Job satisfaction is at the core of every organization's fulfilling of its mission and achieving its goals while providing safeguards to protect organizational resources. The objectives of this study are to evaluate on the prevailing job satisfaction, to identify which factors are mostly influencing the job satisfaction and to recommend a crackdown action and suitable structured changes. Conceptualization model includes promotion, Work it Self, Pay, Working condition to evaluate the job satisfaction in Jaffna DS division. To analyze the job Satisfaction, 65 employees were taken as sample from Jaffna Divisional Secretariat. Data were collected from 65 employees by questionnaires. Method of analysis specifically considered was correlation analysis and Regression analysis. This research would benefit the DS division as well as other organizations. Job Satisfaction and Employees Performance are significantly correlated at 0.01 significant levels. The Correlation value between Job Satisfaction and Employees Performance is 0.638 which is significant at 0.01 levels. Promotion, Work it Self, Pay, and Working Condition are influenced by Employees Performance by 19.5%, 18.7%, 25.5% and 30.08%. Eventually it is evident that this research would provide an awareness to develop the knowledge in applying theories for the researchers and the participants.